Sobre les jocalies de les capelles de la Seu Vella de Lleida (segle XV) = On the jewels of the chapels of the Old Cathedral of Lleida (15th century) - Llevot, Francesc Fité (Miscel·lània litúrgica catalana, 2023)
In this study, we discuss the iocalia or jewels of the chapels of the Seu Vella (Old Cathedral) of Lleida in the 14th-15th centuries, based on a set of inventories that have allowed us to determine their typology and characteristics.